2018
DOI: 10.1002/acp.3483
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the putative confession instruction on perceptions of children's true and false statements

Abstract: The putative confession (PC) instruction (i.e., "[suspect] told me everything that happened and wants you to tell the truth") during forensic interviews with children has been shown to increase the accuracy of children's statements, but it is unclear whether adults' perceptions are sensitive to this salutary effect. The present study examined how adults perceive children's true and false responses to the PC instruction. Participants (n = 299) watched videotaped interviews of children and rated the child's cred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Therefore, the present findings indicate that the children who conceal the transgression in the face of the PC are a particularly convincing group of concealers. In this study and in Gongola et al (2019), accuracy was lower when children concealed in response to the PC (31–37%), than for children who did not hear the PC instructions ( M = 62%, Gongola et al, 2019), or for children in similar deception detection studies ( M = 46% reported in Gongola et al, 2017).…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Therefore, the present findings indicate that the children who conceal the transgression in the face of the PC are a particularly convincing group of concealers. In this study and in Gongola et al (2019), accuracy was lower when children concealed in response to the PC (31–37%), than for children who did not hear the PC instructions ( M = 62%, Gongola et al, 2019), or for children in similar deception detection studies ( M = 46% reported in Gongola et al, 2017).…”
Section: Discussionsupporting
confidence: 59%
“…As a final note, the interview videos used in the present study were also used in the PC conditions in Gongola et al (2019). As shown in Table 3, the accuracy scores were replicated in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations